Synergized Network Asset: A Driver for Indonesia’s Furniture Industries to Elevate Marketing Performance - Ahmad Ikhwan Setiawan; Augusty Tae Ferdinand (International Journal of Business and Society, 2021)
The main focus of this study is developing synergized network asset as a mediator variable for improving marketing performance. The research model was tested using AMOS SEM on 280 local market-oriented furniture makers. The output of the statistical analysis confirms that two buffer variables, namely relational capability and market dynamic adaptability, sustain synergized network asset and marketing performance. However, synergized network asset does not play a strong mediation role in increasing marketing performance. The slow-growing furniture industry is in greater need of responsive rather than synergistic cooperation. The concept of synergized network asset, which is characterized by the sustainability of collaboration quality, contributes to the development of business network theory as one of the main factors in marketing relationships.